5 forest paintball / Khairul Amirin Zulkernain ... [et al.] - Zulkernain, Khairul Amirin; Mohammad Amin, Nuramada Izzati; Che Abdullah, Fahim Aiman; Ramli, Nurul Hazlinda; Mohd Yusof, Muhammad Shahidan (2014)
This business plan is prepared as a guidance for managing the propose business venture for services. Besides that, a guide is very important to assist us in understanding the nature of business and working component of a company, furthermore in preparing this business plan, we need allocate business resources effectively and efficiently, so that, our customer possibly will feel comfortable with our service. We also have list down the plans and strategies of the business in order to achieve the company's goals. This business plan is also prepared to obtain a working capital loan from MARA for an amount RM 90,000